2005
DOI: 10.1890/03-0762
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Lychnis Flos-Cuculi From Fragmented Populations Under Experimental Biotic Interactions

Abstract: Performance of Lychnis flos-cuculi from fragmented populations under experimental biotic interactions AbstractTo study genetic effects of habitat fragmentation on plant performance and plant response to biotic interactions, we performed a greenhouse study with plants from 27 populations of the common plant Lychnis flos-cuculi differing in size, isolation, and microsatellite heterozygosity. We germinated seeds of 449 plants and grew up to nine offspring per maternal plant in single pots assigned to a factorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 47 publications
6
21
0
Order By: Relevance
“…This is in agreement with commonly stated effect of population size on plant performance in fragmented landscapes (Ouborg and van Treuren, 1995;Fischer and Matthies, 1998;Fischer et al, 2000;Galeuchet et al, 2005).…”
Section: Tablesupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with commonly stated effect of population size on plant performance in fragmented landscapes (Ouborg and van Treuren, 1995;Fischer and Matthies, 1998;Fischer et al, 2000;Galeuchet et al, 2005).…”
Section: Tablesupporting
confidence: 92%
“…Hodgkin and Hegarty, 1978;Garbutt and Witcombe, 1986;Girard, 1990;Ouborg and van Treuren, 1995;Fischer and Matthies, 1998;Fischer et al, 2000;Galeuchet et al, 2005; but see Morgan, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, population size, density, and genetic diversity of S. officinalis populations did not influence the response of seedlings to defoliation. Thus, our results are in line with other studies on perennial plants that did not find effects of habitat fragmentation on the ability to respond to stress (Galeuchet et al 2005;Paschke et al 2005) and support the findings of a previous study that indicates a minor importance of fragmentation processes for the fitness of S. officinalis in the study area (Musche et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…High between-population dye dispersal distances (up to 2.4 km) and high reproductive success (higher than in the agricultural landscape) have been also found for Brussels urban populations of the self-incompatible insect-pollinated herb Centaurea jacea (Van Rossum, in press). By contrast, Galeuchet et al (2005aGaleuchet et al ( , 2005b have reported a lower genetic diversity and inbreeding depression leading to reduce fitness in the small populations of L. flos-cuculi from Swiss non-urban fen meadows and suggested higher selfing rates as a result of lower pollinator abundance. Urban areas like Brussels may still offer a good pollinator service, even better than in farmlands, as they may support large population of pollinating insect species such as generalist bumblebees or butterflies, thanks to the high heterogeneity of the urban landscape, which provides many suitable nesting sites and a high floral diversity, and to a low use of pesticides (Chapman et al, 2003;Tommasi et al, 2004;Kadlec et al, 2008;Osborne et al, 2008).…”
Section: Dye Dispersal Patterns and Plant And Recipient Population Trmentioning
confidence: 93%